Impact of Prenatal Stress on Neuroendocrine Programming - Odile Viltart; Christel C. A. Vanbesien-Mailliot (The Scientific World Journal)
Since life emerged on the Earth, the development of efficient strategies to cope with sudden and/or permanent changes of the environment has been virtually the unique goal pursued by every organism in order to ensure its survival and thus perpetuate the species. In this view, evolution has selected tightly regulated processes aimed at maintaining stability among internal parameters despite external changes, a process termed homeostasis. Such an internal equilibrium relies quite heavily on three interrelated physiological systems: the nervous, immune, and endocrine systems, which function as a permanently activated watching network, communicating by the mean of specialized molecules: neurotransmitters, cytokines, and hormones or neurohormones. Potential threats to homeostasis might occur as early as during in utero life, potentially leaving a lasting mark on the developing organism. Indeed, environmental factors exert early-life influences on the structural and functional development of individuals, giving rise to changes that can persist throughout life. This organizational phenomenon, encompassing prenatal environmental events, altered fetal growth, and development of long-term pathophysiology, has been named early-life programming. Over the past decade, increased scientific activities have been devoted to deciphering the obvious link between states of maternal stress and the behavioral, cognitive, emotional, and physiological reactivity of the progeny. This growing interest has been driven by the discovery of a tight relationship between prenatal stress and development of short- and long-term health disorders. Among factors susceptible of contributing to such a deleterious programming, nutrients and hormones, especially steroid hormones, are considered as powerful mediators of the fetal organization since they readily cross the placental barrier. In particular, variations in circulating maternal glucocorticoids are known to impact this programming strongly, notably when hormonal surges occur during sensitive periods of development, so-called developmental windows of vulnerability. Stressful events occurring during the perinatal period may impinge on various aspects of the neuroendocrine programming, subsequently amending the offspring's growth, metabolism, sexual maturation, stress responses, and immune system. Such prenatal stress-induced modifications of the phenotypic plasticity of the progeny might ultimately result in the development of long-term diseases, from metabolic syndromes to psychiatric disorders. Yet, we would like to consider the outcome of this neuroendocrine programming from an evolutionary perspective. Early stressful events during gestation might indeed shape internal parameters of the developing organisms in order to adapt the progeny to its everyday environment and thus contribute to an increased reproductive success, or fitness, of the species. Moreover, parental care, adoption, or enriched environments after birth have been shown to reverse negative long-term consequences of a disturbed gestational environment. In this view, considering the higher potential for neonatal plasticity within the brain in human beings as compared to other species, long-term consequences of prenatal stress might not be as inexorable as suggested in animal-based studies published to date.